Optical and electrochemical effects of triarylamine inclusion to alkoxy BODIPY-based derivatives. (15th September 2021) - Rocha-Ortiz, Juan S.; Insuasty, Alberto; Madrid-Usuga, Duvalier; Mora-León, Ana G.; Ortiz, Alejandro
Abstract : Three new triphenylamine-BODIPY dyads BDPT1–3 have been designed and synthesized. Abstract : Three new triphenylamine-BODIPY dyads BDPT1–3 have been designed and synthesized. Their optoelectronic properties were investigated, which revealed strong electronic interactions between the donor and acceptor moieties, together with high sensitivity to the inclusion of alkoxy groups. The properties of the dyads were compared with those of reference compounds A and BDP1, which exhibit broader absorption in the visible region as a result of the inclusion of donor groups and extended conjugation of the BODIPY core. Fluorescence quenching was also observed, which was attributed to the photoinduced electron transfer, evidenced from solvatochromic measurements, quantum yields and theoretical calculations. The oxidation potentials of new compounds were found to be lower when compared with those of other BODIPY analogues with donor groups attached. The redox, computational, absorbance and emission data suggest that compounds BDPT1–3 exhibit promising properties for their application in organic photovoltaic or light emitting (optoelectronic) devices.